A Wisata Terapung Sebagai Mitigasi Bencana Banjir Rob di Bagan Deli Belawan - AGUS ARIFIN ARIFIN; Novalinda; Rahmadhani Fitri; Faurantina Forlana Sigit (Universitas Medan Area, 2023)
Tidal flooding in coastal areas is a problem that is currently very difficult to solve, especially in the Bagan Deli area of Belawan. Global warming is the main factor in melting the polar ice caps and causing sea levels to rise, when the tide rises to 2.7 meters above sea level, which temporarily stops the activities and economy of residents in the Bagan Deli Belawan area. This study aims to solve problems and obtain design solutions with the concept of floating tourism to prevent tidal water due to tidal flooding into residential areas. The research method uses the hull engineering design method (Hull) as a floating medium above which will be made into a tourist area and linked to an experimental electromechanical module (MOSE) to prevent tidal flood waters from entering residential areas, so that tourist areas are not washed away. The results of this study will be a recommend for the concept of preventing tidal flooding in all residential areas in coastal areas.